FINANCIAL INCLUSION (FI): KINERJA UMKM DI INDONESIA DARI PUBLISH OR PERISH - Jeprianto, Eeng; Satria, Chandra (Institut Agama Islam Negeri Kerinci, 2024)
Purpose: This study aims to analyze the financial inclusion of Micro, Small, and Medium Enterprises (MSMEs) that are currently supporting economic growth in Indonesia. Design/Methodology/Approach: Systematic Literature Review (SLR) is a method in this observation by reviewing certain topics of discussion that focus on specific problems that have been identified and classified in a structured manner, assessed, concluded, and selected based on previously determined benchmarks based on evidence and facts from quality research that is relevant to the research question. Research data was obtained from Google Scholar for the period 2011-2022 based on the initial search, there were 198 articles, and only 25 articles were used as data sources and will be studied in more depth. Findings: The results of the research show that through investment diversification, risk management, and wise financial planning, individuals and companies can reduce the negative impact of economic impacts and maintain their financial stability. Research Implications: Insulation can help MSMEs protect their businesses from market shocks, interest rate changes, or other external impacts that can be detrimental. Financial inclusion after the economic crisis that occurred in 2008 hurt financial stability in Indonesia.